An Updated Insight Into Molecular Mechanism of Hydrogen Sulfide in Cardiomyopathy and Myocardial Ischemia/Reperfusion Injury Under Diabetes - Sun, Hai-Jian; Wu, Zhi-Yuan; Nie, Xiao-Wei; Wang, Xin-Yu; Bian, Jin-Song (Frontiers in Pharmacology, 2021)
Cardiovascular diseases are the most common complications of diabetes, and diabetic cardiomyopathy is a major cause of people death in diabetes. Molecular, transcriptional, animal, and clinical studies have discovered numerous therapeutic targets or drugs for diabetic cardiomyopathy. Within this, hydrogen sulfide (H2S), an endogenous gasotransmitter alongside with nitric oxide (NO) and carbon monoxide (CO), is found to play a critical role in diabetic cardiomyopathy. Recently, the protective roles of H2S in diabetic cardiomyopathy have attracted enormous attention. In addition, H2S donors confer favorable effects in myocardial infarction, ischaemia-reperfusion injury, and heart failure under diabetic conditions. Further studies have disclosed that multiplex molecular mechanisms are responsible for the protective effects of H2S against diabetes-elicited cardiac injury, such as anti-oxidative, anti-apoptotic, anti-inflammatory, and anti-necrotic properties. In this review, we will summarize the current findings on H2S biology and pharmacology, especially focusing on the novel mechanisms of H2S-based protection against diabetic cardiomyopathy. Also, the potential roles of H2S in diabetes-aggravated ischaemia-reperfusion injury are discussed.